2022
DOI: 10.1039/d2ta02774g
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate-based hyper-cross-linked polymers with pendant versatile electron-withdrawing functional groups for CO2adsorption and separation

Abstract: Simple and highly efficient preparation of porous hyper-cross-linked polymers (HCPs) with high surface area and manifold functionalities for high-performance CO2 uptake and selective separation has drawn multitudinous attention over the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…3.2.2 CO 2 /CH 4 selectivity. Hou et al 48 designed a strategy to knit together carbonate-based HCPs. The hydroxyl groups in the carbonates, for which a hydrogen atom is partially or completely substituted by an alkyl group, are Lewis basic sites in the polymer and can enhance the specific interaction with CO 2 .…”
Section: Selective Co 2 Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…3.2.2 CO 2 /CH 4 selectivity. Hou et al 48 designed a strategy to knit together carbonate-based HCPs. The hydroxyl groups in the carbonates, for which a hydrogen atom is partially or completely substituted by an alkyl group, are Lewis basic sites in the polymer and can enhance the specific interaction with CO 2 .…”
Section: Selective Co 2 Adsorptionmentioning
confidence: 99%
“…45 In recent years, porous organic polymers (POPs) have emerged as excellent adsorption and conversion materials. [46][47][48] Not only do they integrate the advantages of the above materials, but they are also expected to solve their disadvantages. The synthesis of POPs is usually carried out with special conditions, complex monomers for the covalent organic frame-works (COFs), [49][50][51] noble metal catalysts for conjugated microporous polymers (CMPs), 52,53 and an inert atmosphere for porous aromatic frameworks (PAFs) and polymers of intrinsic microporosity (PIMs), 54,55 all of which limit their industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, Zhou et al have synthesized a series of HCPs of intrinsic microporosity (PIM), which display a CO 2 capture capacity of 6.7 mmol g −1 and a CO 2 HCP/N 2 selectivity of 26.5 at 298 K. 30 Hou et al reported a CO 2 capture capacity and a CO 2 /N 2 selectivity of 3.3 mmol g −1 and 20.1, respectively, at 273 K using a carbonate-based HCP as the adsorbent. 31 Begni and co-workers provided evidence regarding the function of PIMs in mitigating the aging effects of PIM-based mixed matrix membranes. 32 Moreover, because of the presence of extensive π electrons, the HCPs are believed to adsorb aromatic organic molecules like organic dyes by π−π interaction.…”
Section: Introductionmentioning
confidence: 99%
“…8 Over the past two decades, nanoporous materials (NPMs) have become key materials for enhancing membrane separation performance. Zeolites, 9 metal−organic frameworks (MOFs), 10 and porous polymer networks (PNNs) 11 have been widely investigated and exhibited good separation performance.…”
Section: Introductionmentioning
confidence: 99%